2017
DOI: 10.1111/jvim.14833
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Consequences of Hypertriglyceridemia‐Associated Proteinuria in Miniature Schnauzers

Abstract: BackgroundPrimary hypertriglyceridemia is a common condition in older Miniature Schnauzers that recently has been associated with proteinuria and underlying glomerular pathology, particularly glomerular lipid thromboemboli. Consequences of glomerular disease can include hypertension, thromboembolic disease, and cardiac disease. The incidence of these sequelae in Miniature Schnauzers with hypertriglyceridemia‐associated proteinuria (HTGP) is unknown.ObjectiveTo investigate prevalence of hypertension, decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
1
19
1
Order By: Relevance
“…Thus, further studies are warranted to evaluate if macrophage and neutrophil hyperactivity accounts for the increased serum S100/calgranulin concentrations in MS with IH. Further research also is warranted to determine whether this presumed low‐grade inflammatory phenotype in MS with IH contributes to or reflects the development of possible complications of IH, and to test the alternative hypothesis that the hypercalprotectinemia in MS with IH reflects an anti‐inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, further studies are warranted to evaluate if macrophage and neutrophil hyperactivity accounts for the increased serum S100/calgranulin concentrations in MS with IH. Further research also is warranted to determine whether this presumed low‐grade inflammatory phenotype in MS with IH contributes to or reflects the development of possible complications of IH, and to test the alternative hypothesis that the hypercalprotectinemia in MS with IH reflects an anti‐inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic HTGL in MS has been reported to be associated with proteinuria and ultrastructural glomerular lesions, but whether these findings are a consequence or cause of dyslipidemia in MS remains unknown. Presence of proteinuria (ie, urine protein/creatinine ratios) or renal biopsy specimens were not evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Each unit increase in the severity of illness was associated with a 173% increase in odds of a urine dipstick protein concentration to USG ratio ≥1.5 (P = .04; Figure 2). Hyperadrenocorticism is known to be associated with proteinuria in dogs 4,5,17 and is a common comorbidity in dogs with mucocele formation. 8,9,12 Lack of association between proteinuria and hyperadrenocorticism in our study likely is related to selection criteria that decreased the number of dogs ultimately diagnosed with hyperadrenocorticism.…”
Section: Illness Severitymentioning
confidence: 99%
“…Likewise, dyslipidemia has been detected in patients diagnosed with IBD [3537]. Similar to the findings in humans, altered lipid profiles have been recognized in dogs diagnosed with idiopathic hyperlipidemia [38,39], diabetes mellitus [40], parvoviral infection [41], cancer [42], renal disease [43,44], or systemic infections [45]. Besides possibly contributing to the pathogenesis of those diseases, several studies have demonstrated lipids, in particular polyunsaturated fatty acids (PUFA), to also have immunomodulatory, anti-inflammatory, and potentially other beneficial effects both in human [4648] and in veterinary patients [49,50].…”
Section: Introductionmentioning
confidence: 79%